2020
DOI: 10.1038/s41598-020-59125-w
|View full text |Cite
|
Sign up to set email alerts
|

Early-life microbiota transplantation affects behavioural responses, serotonin and immune characteristics in chicken lines divergently selected on feather pecking

Abstract: in life 17. These findings suggest that the gut microbiota influences behavioural and physiological characteristics in poultry and could therefore influence a bird's ability to cope with environmental and social challenges, such as those encountered in animal production systems. Excessive damaging behaviours are indicative of an animal's inability to cope with a restrictive environment and are frequently seen in production animals. Feather pecking (FP) in chickens is one such damaging behaviour, which involves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 87 publications
3
37
0
Order By: Relevance
“…The authors detected common genomic regions for the presence of bacteria such as Lactobacillus and L. crispatus and traits such as feeding behavior (Mignon-Grasteau et al, 2017). A pilot study investigated the effects of early-life microbiota transplantation on feather pecking, and behavioral and physiological traits related to feather pecking (van der Eijk et al, 2020). The researchers reported that chicken lines with divergent genetic merit for feather pecking had different microbiota composition.…”
Section: Microbiota Profilingmentioning
confidence: 99%
“…The authors detected common genomic regions for the presence of bacteria such as Lactobacillus and L. crispatus and traits such as feeding behavior (Mignon-Grasteau et al, 2017). A pilot study investigated the effects of early-life microbiota transplantation on feather pecking, and behavioral and physiological traits related to feather pecking (van der Eijk et al, 2020). The researchers reported that chicken lines with divergent genetic merit for feather pecking had different microbiota composition.…”
Section: Microbiota Profilingmentioning
confidence: 99%
“…It has been suggested that the increased inflammatory state seen in depressed individuals (humans) is due to a response to LPS in intestinal bacteria that reach the circulation due to increased permeability in the intestinal wall ( 180 , 181 ). Hens with high and low levels of repetitive feather-pecking behavior have differences in intestinal microbial metabolites ( 182 ), but transplantation of gut microbiota from the high to low feather pecker line and vice versa did not have a strong effect on microbiota nor on feather pecking ( 183 ). A recent report showed more lactobacilli in the gut microbiota of pigs that neither bit nor were bitten compared to biters and victims (Rhabi et al, under review).…”
Section: Risk Factors For Tail Biting In Pigs and Their Relationship mentioning
confidence: 99%
“…In broiler, L-tryptophan supplementation could relieve stress-effected expression of IL-1, IL-6, IL-10, and TNF-α by regulating 5-HT metabolism (Yue et al, 2017) and increase serum IgM concentration quadratically in laying hen reared under hot and humid summer conditions (Dong et al, 2012). Except of the behavioral responses, earlylife microbiota transplantation has long-term effects on immune characteristics and peripheral serotonin of chicken in a genotypedependent way (van der Eijk et al, 2020). As the intermediate metabolite of the essential amino acid L-tryptophan in the biosynthesis of 5-HT, 5-Hydroxytryptophan (5-HTP) has been used as a clinically effective serotonin precursor (Birdsall, 1998).…”
Section: Introductionmentioning
confidence: 99%